COMPARISON OF FLEXIBLE URETERORENOSCOPY AND LAPAROSCOPIC URETEROLITHOTOMY METHODS FOR PROXIMAL URETERIC STONES GREATER THAN 10 MM. - Cavildak, Idris Kivanc; Nalbant, Ismail; Tuygun, Can; Ozturk, Ufuk; Goksel Goktug, Hasan Nedim; Bakirtas, Hasan; Imamoglu, Muhammed Abdurrahim (Urology Journal, 2016)
Objective: To examine the outcomes and to compare the effectiveness of laparoscopic ureterolithotomy and flexible URS in patients with proximal ureteral stones greater than 10 mm in diameter. Material and Methods: A total of 150 patients who were performed laparoscopic ureterolithotomy and flexible URS because of uretral stones in our urology clinic between January 2010 and June 2015, were analyzed retrospectively. We constituted two groups; 70 patients who were performed laparoscopic ureterolithotomy were included in group I while flexible URS-performed 80 patients in group II. Success rates and complications of the group I and II were compared. Results: Succes rates were 95.7% and 90% in group I and II respectively. There was no significant difference between the groups in terms of "success-rates". No statistically and clinically significant complications occured in both groups. Conclusion: Laparoscopic ureterolithotomy and flexible URS methods are effective and reliable with proper indications in treatment of proximal ureteral stones. However, when considered short operational and hospitalization times and the management of the situations that require secondary interventions, we suggest that flexible URS is a minimally invasive method and it may be the first choice in the treatment of proximal ureteral stones.